Disabilities and Child Welfare: Ensuring Equal Rights and Opportunities: A Case Study of Punjab, Pakistan - Rafi, Sadia; Ali, Mumtaz (Social Science Review Archives, 2025)
This study investigates the realization of equal rights and opportunities for children with disabilities within child welfare institutions in Punjab. Grounded in a rights-based framework consistent with the United Nations Convention on the Rights of Persons with Disabilities (CRPD), the research examines how legislative commitments are translated into institutional practices and service delivery mechanisms. The primary objectives of the study were to assess the extent of policy implementation, identify structural and socio-cultural barriers affecting inclusion, evaluate institutional capacity and coordination, and explore emerging practices that promote disability-inclusive child welfare. By focusing on both systemic structures and lived experiences, the study aimed to provide a comprehensive understanding of inclusion gaps and reform opportunities. A qualitative case study design was employed to generate in-depth insights into institutional realities. Data were collected through semi-structured interviews with policymakers, social workers, educators, rehabilitation professionals, and caregivers, complemented by document analysis of relevant provincial policies, child protection laws, and institutional reports. Purposive sampling was used to select information-rich participants, and data collection continued until thematic saturation was achieved. Thematic analysis guided the interpretation of data, enabling the identification of recurring patterns, sub-themes, and contextual dynamics related to accessibility, protection mechanisms, professional competence, and social attitudes. Credibility and trustworthiness were ensured through triangulation, member checking, and careful documentation of analytical procedures. The findings reveal a substantial gap between policy recognition and effective implementation, primarily due to weak enforcement mechanisms, inadequate budget allocations, fragmented interdepartmental coordination, and limited specialized training. Structural barriers such as inaccessible infrastructure, economic constraints, and rural-urban disparities further restrict access to education, healthcare, and rehabilitation services. Additionally, stigma and gender-based discrimination exacerbate exclusion, particularly for girls with disabilities. However, inclusive education initiatives and community-based rehabilitation programs demonstrate promising progress. The study concludes that sustainable realization of equal rights requires systemic reforms, strengthened accountability mechanisms, professional capacity building, and enhanced community awareness to ensure meaningful inclusion within Punjab’s child welfare framework.